Manufacturing method of large-current high-shielding flexible circuit board for intelligent connected vehicle
Patent Information
- Application Number
- CN202611106957.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明旨在解决现有技术存在的厚铜柔性电路板因铜厚≥105μm导致覆盖膜表面凹凸不平,进而引发的银浆屏蔽层印刷不均、易开裂及屏蔽效果不稳定的问题,提供一种智能网联汽车用大载流高屏蔽柔性电路板的制作方法,可以提升屏蔽层均匀性与完整性,避免压合开裂;增强层间结合力与表面平整度,确保电磁屏蔽性能稳定可靠
本发明的智能网联汽车用大载流高屏蔽柔性电路板的制作方法,通过将银浆屏蔽层前置制作于平整的覆盖膜上,使屏蔽层在无凹凸干扰的环境中印刷固化,保证了银浆的均匀性和完整性,且被覆盖膜封装后在后续压合中受力缓冲,避免了开裂风险。同时,采用液态胶黏剂填充厚铜线路间隙,在抽真空条件下充分流动并预固化,消除了线路间的落差,使表面趋于平整,大幅提高了层间结合力和结构可靠性。最终产品不仅屏蔽性能一致、稳定,而且具有优异的耐弯折性和热可靠性,能够满足智能网联汽车对高载流、高屏蔽柔性电路板的严苛要求。
Smart Images

Figure CN122995040A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of circuit board processing, and in particular to a method for manufacturing a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles. Background Technology
[0002] With the rapid development of intelligent connected vehicles, higher requirements are being placed on the integration, current carrying capacity, and electromagnetic compatibility of electronic components. Flexible circuit boards are widely used due to their advantages such as lightweight and bendability, especially in power transmission modules that need to carry high currents, where single-layer thick copper flexible circuit boards with a copper thickness of ≥105μm are often used. To meet electromagnetic shielding requirements, these products typically require the printing of silver paste on the circuit surface to form a shielding layer.
[0003] In existing technologies, a typical manufacturing process involves: first, forming a thick copper circuit pattern on a single-sided thick copper flexible copper-clad laminate using a pattern transfer process; then, laminating a layer of adhesive-coated cover film to wrap the circuit; next, subjecting the cover film surface to plasma activation treatment; then, printing silver paste onto the activated uneven surface to form a shielding layer; and finally, laminating another cover film to protect the silver paste layer. However, due to the large copper thickness (≥105μm) and the relatively thin cover film, significant unevenness is generated on the surface of the circuit area after lamination. Directly printing silver paste onto the uneven cover film surface after wrapping the circuit makes it difficult to guarantee the uniformity of the silver paste thickness and distribution; moreover, during the subsequent lamination of the protective cover film, the pressure can easily cause the silver paste covering the top of the raised circuit to crack due to stress concentration, resulting in damage to the shielding layer and ultimately leading to unreliable and inconsistent electromagnetic shielding effects.
[0004] Therefore, how to solve the problem of surface unevenness caused by thick copper lines and improve the uniformity and structural reliability of the shielding layer has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] This invention aims to solve the problems existing in the prior art where thick copper flexible circuit boards with a copper thickness ≥105μm have uneven surfaces on the cover film, leading to uneven printing of the silver paste shielding layer, easy cracking, and unstable shielding effect. It provides a method for manufacturing a high current-carrying, high-shielding flexible circuit board for intelligent connected vehicles, which can improve the uniformity and integrity of the shielding layer, avoid pressing cracks, enhance interlayer bonding and surface flatness, and ensure stable and reliable electromagnetic shielding performance.
[0006] This invention provides a method for manufacturing a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles, the method comprising: The first cover film is subjected to plasma activation treatment, and the first cover film is an adhesive-free cover film. A silver paste shielding layer is formed on the surface of the first cover film after activation treatment, and the silver paste shielding layer is encapsulated between the first cover film and the second cover film with a second cover film to form a first functional cover film with a shielding structure. Thick copper foil is laminated onto one side of the first functional covering film using an adhesive layer; The laminated thick copper foil is subjected to pattern transfer and etching to form a thick copper circuit pattern; Liquid adhesive is printed on the surface where thick copper circuit patterns are formed, so that the liquid adhesive fills the gaps between the thick copper circuits, and pre-baking is performed to make it reach a semi-cured state. A second functional cover film with a shielding structure is fabricated, the structure of the second functional cover film being the same as that of the first functional cover film; The second functional cover film is stacked on the surface of the pre-baked liquid adhesive and pressed together to combine the second functional cover film, the thick copper circuit layer and the first functional cover film into one, forming a flexible circuit board structure.
[0007] Furthermore, the step of forming a silver paste shielding layer on the surface of the first cover film after activation treatment, and encapsulating the silver paste shielding layer between the first cover film and the second cover film with a second cover film, includes: The first cover film, after being activated by plasma, is placed on a support plate, and silver paste is printed on the surface of the first cover film to form a shielding layer. The printed silver paste is baked and cured; A second cover film is attached to the surface of the cured silver paste layer. The second cover film is an adhesive cover film, so that the silver paste layer is encapsulated between the first cover film and the second cover film. Remove the support plate to form a first functional cover film with a shielding structure.
[0008] Furthermore, the process parameters for the plasma activation treatment are as follows: Processing power 80-150W, processing time 3-5 minutes, working gas is oxygen, argon or a mixture of oxygen and argon, gas flow rate 50-200sccm, working pressure 50-200mTorr.
[0009] Furthermore, The thickness of the silver paste layer is 8-15 μm. The conditions for baking and curing the printed silver paste are as follows: bake and cure at 120-150℃ for 10-30 minutes.
[0010] Furthermore, the thickness of the printed wet film of the liquid adhesive is 0.5-0.8 times the thickness of the thick copper foil, and its viscosity is 5-15 Pa·s at 25°C.
[0011] Furthermore, the vacuum degree of the vacuum treatment is controlled at ≤-0.08MPa gauge pressure or ≤20Pa absolute pressure, and the pressure holding time is 3-5 minutes.
[0012] Furthermore, the pre-baking conditions are as follows: Baking temperature: 80-100℃, time: 5-15 minutes.
[0013] Furthermore, after plasma activation treatment and before printing silver paste, the surface contact angle of the first cover film is reduced to below 30°.
[0014] Furthermore, after the liquid adhesive is filled and pressed, the surface flatness reaches ≤10μm / 10mm, and there are no air bubbles or voids.
[0015] Furthermore, the liquid adhesive is a liquid acrylic adhesive or epoxy resin adhesive.
[0016] The main beneficial effects of this technical solution are: The present invention discloses a method for manufacturing a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles. By pre-fabricating a silver paste shielding layer on a flat cover film, the shielding layer is printed and cured in an environment free from unevenness, ensuring the uniformity and integrity of the silver paste. Furthermore, the cover film provides stress buffering during subsequent pressing, avoiding the risk of cracking. Simultaneously, liquid adhesive is used to fill the gaps between thick copper lines, allowing it to flow fully and pre-cur under vacuum conditions. This eliminates unevenness between lines, resulting in a smoother surface and significantly improving interlayer bonding and structural reliability. The final product not only exhibits consistent and stable shielding performance but also excellent bending resistance and thermal reliability, meeting the stringent requirements of intelligent connected vehicles for high-current-carrying, highly shielded flexible circuit boards. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0018] Figure 1 This is a schematic diagram of the manufacturing process of a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles according to an embodiment of the present invention. Figure 2 This is a schematic diagram of the first covering film according to an embodiment of the present invention; Figure 3 This is a schematic diagram illustrating the process of applying a cover film to a support plate for screen printing silver paste according to an embodiment of the present invention. Figure 4This is a schematic diagram illustrating how a silver paste shielding layer is encapsulated between a first cover film and a second cover film according to an embodiment of the present invention. Figure 5 This is a schematic diagram of a product after the first functional cover film and thick copper foil are laminated according to an embodiment of the present invention. Figure 6 This is a schematic diagram of a thick intermediate product fabricated using a thick copper circuit pattern according to an embodiment of the present invention. Figure 7 This is a schematic diagram of an intermediate product after printing and pre-curing of the liquid adhesive according to an embodiment of the present invention; Figure 8 This is a schematic diagram of the overall pressing process according to an embodiment of the present invention; Figure 9 This is a schematic diagram of the structure of the final product according to an embodiment of the present invention; Figure 10 A physical cross-sectional view of a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles manufactured for an embodiment of the present invention; Figure 11 Enlarged cross-sectional view of a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles manufactured for an embodiment of the present invention.
[0019] Explanation of reference numerals: 10, First functional cover film; 100, First cover film; 200, Silver paste shielding layer; 300, Support plate; 400, Second cover film; 501, Thick copper foil; 502, Thick copper circuit layer; 600, Adhesive layer; 700, Liquid adhesive layer; 801, Release film; 802, Replica film; 803, Steel plate; 20, Second functional cover film.
[0020] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0022] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.
[0023] Furthermore, in this invention, descriptions involving "first," "second," etc., are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0024] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are feasible for those skilled in the art. If the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.
[0025] To better understand the above technical solution, a detailed explanation of the technical solution is provided below with reference to the accompanying drawings.
[0026] Please see Figure 1 , Figure 1 This is a process flow diagram of an embodiment of the present invention.
[0027] A method for manufacturing a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles, the method comprising: Step S100: Perform plasma activation treatment on the first cover film, wherein the first cover film is an adhesive-free cover film.
[0028] Step S200: A silver paste shielding layer is formed on the surface of the first cover film after activation treatment, and the silver paste shielding layer is encapsulated between the first cover film and the second cover film with a second cover film to form a first functional cover film with a shielding structure.
[0029] Step S300: The thick copper foil is pressed onto one side of the first functional cover film using an adhesive layer.
[0030] Step S400: The thick copper foil after lamination is subjected to pattern transfer and etching to form a thick copper circuit pattern.
[0031] Step S500: Print liquid adhesive on the surface where the thick copper circuit pattern is formed, so that the liquid adhesive fills the gaps between the thick copper circuits, and pre-bake it to achieve a semi-cured state.
[0032] Step S600: Fabricate a second functional cover film with a shielding structure, the structure of which is the same as that of the first functional cover film.
[0033] Step S700: The second functional cover film is stacked on the surface of the pre-baked liquid adhesive and pressed together to combine the second functional cover film, the thick copper circuit layer and the first functional cover film into one, forming a flexible circuit board structure.
[0034] This disclosure aims to provide a method for manufacturing a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles, solving the technical problems in the prior art where the unevenness of the cover film surface caused by thick copper lines (copper thickness ≥ 105 μm) leads to uneven printing of the silver paste shielding layer, easy cracking, and unstable shielding effect. By reconstructing the process flow, the shielding layer is placed in a flat environment before fabrication; and liquid adhesive is used to fill the gaps between the lines, making the subsequent lamination surface more flat, ultimately achieving a uniform and complete shielding layer, high structural reliability, and consistent electromagnetic shielding performance.
[0035] This embodiment provides a method for manufacturing a high current-carrying, highly shielded flexible circuit board for intelligent connected vehicles. The specific steps are as follows: Step S100: Plasma activation treatment of the first covering film: like Figure 2 As shown, in this embodiment of the invention, a 25 μm thick adhesive-free polyimide (PI) cover film is selected as the first cover film 100. Due to the strong inertness of polyimide, it is placed in a plasma treatment device for plasma treatment. Oxygen is used to increase the surface polar groups, and argon gas is used for physical bombardment to increase the roughness, thereby increasing the adhesion between the cover film surface and the shielding layer.
[0036] Furthermore, the process parameters for the plasma activation treatment are as follows: Processing power 80-150W, processing time 3-5 minutes, working gas is oxygen, argon or a mixture of oxygen and argon, gas flow rate 50-200sccm, working pressure 50-200mTorr.
[0037] The above parameter range (power 80-150W, time 3-5 minutes) is determined based on the material properties of the PI film and industrial practice experience. Power below 80W may result in insufficient activation, while power above 150W poses a risk of thermal damage; a time shorter than 3 minutes is insufficient, while a time exceeding 5 minutes reduces efficiency and may lead to over-etching. Gas flow rate and operating pressure must be matched to the equipment cavity to ensure uniform and stable plasma.
[0038] In a preferred embodiment, the plasma treatment process parameters are set as follows: treatment power 100W, treatment time 4 minutes, working gas is a mixture of oxygen and argon (volume ratio 1:1), gas flow rate 100 sccm, and working pressure 100 mTorr. This parameter combination adopts a "low power + moderate time" design, which avoids thermal damage to the PI film caused by high power (PI film is a heat-sensitive material, and excessive power can easily lead to deformation or embrittlement), while ensuring the uniformity and sufficiency of the activation effect by extending the treatment time. The use of a mixture of oxygen and argon can simultaneously exert the chemical modification effect of oxygen (introducing polar groups) and the physical bombardment effect of argon (increasing surface micro-roughness), synergistically improving the adhesion between the surface energy of the cover film and the subsequent silver paste. After treatment, the surface activity of the cover film is significantly improved.
[0039] The surface activity of the cover film after plasma activation treatment will decrease over time. It is recommended to complete the silver paste printing within 24 hours after activation, or store it in a clean and dry environment for short-term preservation. If necessary, a second activation treatment can be performed.
[0040] Furthermore, after plasma activation treatment and before printing silver paste, the surface contact angle of the first cover film is reduced to below 30°.
[0041] After the treatment, the surface characteristics of the first cover film 100 were tested using a contact angle meter. The test showed that its surface contact angle had dropped to below 30° (the contact angle of untreated PI film is usually greater than 60°), indicating that the surface activity was significantly improved, which provided a good wettability and adhesion foundation for subsequent silver paste printing.
[0042] Step S200: Preparation of the first functional coating film: A silver paste shielding layer is formed on the surface of the first cover film after activation treatment, and the silver paste shielding layer is encapsulated between the first cover film and the second cover film using a second cover film.
[0043] The silver paste is printed and cured on an independent, flat cover film, resulting in good uniformity and integrity. It is first encapsulated by the cover film and then buffered by the force during the subsequent pressing process, thus avoiding cracking due to direct pressure.
[0044] Furthermore, the step of forming a silver paste shielding layer on the surface of the first cover film after activation treatment, and encapsulating the silver paste shielding layer between the first cover film and the second cover film with a second cover film, includes: The first cover film, after being activated by plasma, is placed on a support plate, and silver paste is printed on the surface of the first cover film to form a shielding layer. The printed silver paste is baked and cured; A second cover film is attached to the surface of the cured silver paste layer. The second cover film is an adhesive cover film, so that the silver paste layer is encapsulated between the first cover film and the second cover film. Remove the support plate to form a first functional cover film with a shielding structure.
[0045] Since both the cover film and the printed silver paste shielding layer are relatively thin, a support plate is used to support the cover film to prevent wrinkles during transport and curing, ensuring that the cover film remains flat during operation. The support plate can be FR4, copper-clad laminate, or stainless steel; the support plate is approximately 1.5mm thick with a flat surface, providing a flat and rigid support base for the cover film, ensuring that the cover film remains flat and wrinkle-free during subsequent printing.
[0046] Please refer to Figure 3 , Figure 3 This diagram illustrates the process of screen printing silver paste onto a support plate after attaching a cover film to it. The first cover film 100, after plasma activation treatment, is smoothly attached to the support plate 300. A silver paste shielding layer 200 is then printed onto the surface of the first cover film attached to the support plate using screen printing. In a preferred embodiment, a 200-mesh stainless steel screen is used, and the silver paste is a low-temperature curing silver paste suitable for flexible circuit boards, generally meeting the requirements of a viscosity of approximately 20 Pa·s at 25°C and a solid content ≥85%. During printing, the squeegee pressure is controlled at 0.2-0.3 MPa, and the printing speed is 100-150 mm / s to ensure uniform transfer of the silver paste to the cover film surface.
[0047] Furthermore, the thickness of the silver paste layer is 8-15 μm, and the conditions for baking and curing the printed silver paste are to bake and cure at 120-150℃ for 10-30 minutes.
[0048] The thickness of the silver paste layer is 8-15μm, preferably controlled at around 12μm after printing. The cover film printed with silver paste, along with the support plate, is placed in a hot air circulating oven for baking and curing. The curing temperature is set at 120-150℃, preferably 130℃, and the holding time is 10-30 minutes, preferably 20 minutes. This combination of temperature and time ensures that the solvent in the silver paste evaporates fully and the resin is completely cross-linked and cured, without exceeding the temperature tolerance of the PI film (long-term temperature tolerance of PI film > 300℃). After curing, the surface of the silver paste layer is uniform and dense, without pinholes or cracks. Its adhesion is tested to reach level 5B (no peeling in the cross-cut adhesion test), and its sheet resistance is ≤0.05Ω / □, meeting the conductivity requirements of the electromagnetic shielding layer.
[0049] After the silver paste layer has completely cured and cooled to room temperature, take a layer of adhesive-coated cover film as the second cover film. The thickness can be selected according to requirements, generally 25μm. The substrate of this cover film is a PI film, and the adhesive layer is an acrylic adhesive with a thickness of 12.5μm. Place the second cover film with the adhesive side down, align it with the surface of the cured silver paste layer, and gently press it together using a high-speed press, vacuum high-speed press, or laminator to ensure that there are no air bubbles remaining between the second cover film and the silver paste layer. Figure 4 This is a schematic diagram showing the silver paste shielding layer encapsulated between the first and second cover films via a second cover film, as shown. Figure 4 As shown, at this point, the silver paste shielding layer 200 is completely encapsulated between the first cover film 100 (adhesive-free PI film) and the second cover film 400 (adhesive-coated PI film), forming a sandwich structure. Finally, the support plate 300 is peeled off, and the encapsulated cover film is carefully peeled off from the support plate to obtain the independent first functional cover film. After peeling, the film surface should be flat and undamaged, and the silver paste layer should not be displaced or detached. The structure of the first functional cover film from top to bottom is as follows: second cover film 400 (adhesive-coated PI film), silver paste shielding layer 200, and first cover film 100 (adhesive-free PI film), wherein the silver paste layer is completely covered and protected, and will not be directly exposed or damaged in subsequent processing.
[0050] To ensure a good bonding effect, the first functional cover film after lamination can also be baked in a conventional manner.
[0051] Step S300: Lamination of thick copper foil: Products after laminating thick copper foil, such as Figure 5 As shown. The manufacturing process involves taking a thick copper foil 501, typically with a thickness greater than or equal to 105 μm. An adhesive layer 600 is placed on one side of the first functional cover film 10 (preferably the side of the cover film that has undergone plasma treatment, with the first cover film pressed in the middle). The adhesive layer 600 is a pure adhesive film or a semi-cured sheet, with an adhesive layer thickness typically between 12.5 and 25 μm. The thick copper foil 501 is then placed over the adhesive layer 600, aligned, and fed into a press for pressing. The pressing process parameters are those for conventional copper foil pressing, such as a temperature of 170°C, a pressure of 2.0 MPa, and a time of 90 minutes. During the pressing process, the adhesive layer of the adhesive layer 600 melts, flows, and solidifies, ensuring a tight bond between the thick copper foil 501 and the first functional cover film 100. After pressing, the peel strength should be ≥0.8 N / mm, and the copper foil surface should be smooth and wrinkle-free, providing a good foundation for subsequent circuit fabrication.
[0052] Step S400: Fabrication of thick copper circuit patterns: The laminated thick copper foil 501 undergoes a conventional pattern transfer process: dry film lamination, exposure, development, and then etching. An acidic copper chloride system is used as the etching solution. The pattern fabrication process is the same as existing methods, with parameters controlled according to the copper thickness and production line conditions, and the lateral etching depth controlled to ≤25μm. After etching, a thick copper circuit layer 502 with the desired pattern is formed, with linewidth tolerance controlled within ±10%. The completed intermediate product is as follows... Figure 6 As shown.
[0053] Step S500: Printing and pretreatment of liquid adhesive: A liquid adhesive (commonly known as water-based adhesive in the PCB manufacturing industry), i.e., liquid acrylic or epoxy resin adhesive, is printed on the surface of the thick copper circuit layer 502 with the pattern formed. Liquid acrylic adhesive is preferred as the water-based adhesive. The viscosity of this adhesive at 25°C is approximately 10 Pa·s, and the solid content is ≥95%. Screen printing is used, and for a 105 μm thick copper foil, the wet film thickness is controlled at 60 μm. In a preferred embodiment, the product can be placed in a vacuum chamber immediately after printing, and the vacuum level is ≤-0.08 MPa (gauge pressure), held for 4 minutes to allow the adhesive to fully flow into the gaps between the thick copper circuits and remove air bubbles. Then, pre-baking is performed at 90°C for 10 minutes to bring the adhesive to a semi-cured state (B-stage). At this point, the adhesive has filled the gaps between the circuits but is not yet fully cured, and the surface has a certain degree of tackiness. The pre-cured product is as follows: Figure 7 As shown, a liquid adhesive layer 700 is formed in the gap between the lines and on the surface of the lines.
[0054] Furthermore, the thickness of the printed wet film of the liquid adhesive is 0.5-0.8 times the thickness of the thick copper foil, and its viscosity is 5-15 Pa·s at 25°C.
[0055] The printing process employs screen printing, with the wet film thickness determined based on the thickness of the thick copper foil, controlled to be 0.5-0.8 times the thickness of the thick copper foil. In this embodiment, the thickness of the thick copper foil is 105μm, therefore the wet film thickness is controlled at approximately 60μm (about 0.57 times the copper thickness). This ratio range has been experimentally verified to ensure sufficient adhesive to completely fill the gaps between the lines during subsequent lamination, while avoiding excessive adhesive leading to overflow or uneven thickness. This allows the liquid adhesive to flow and redistribute fully during lamination, completely filling the gaps between the thick copper lines, while maintaining a continuous thin adhesive layer on the copper wire surface for bonding with the second functional cover film. Ultimately, this achieves a bubble-free, void-free filling effect and a surface smoothness of ≤10μm / 10mm.
[0056] Furthermore, the vacuum degree of the vacuum treatment is controlled at ≤-0.08MPa gauge pressure or ≤20Pa absolute pressure, and the pressure holding time is 3-5 minutes.
[0057] After printing, the product is immediately placed in a vacuum press for vacuum degassing. The vacuum level is controlled at ≤-0.08MPa gauge pressure (equivalent to ≤20Pa absolute pressure), and held under this negative pressure for 3-5 minutes (4 minutes is preferred in this embodiment). The purpose of vacuum treatment is to completely remove air from the deep gaps in the thick copper lines at room temperature using negative pressure, while simultaneously promoting the liquid adhesive to fully flow into every corner of the line gaps under the pressure difference, ensuring a dense filling without any air bubbles.
[0058] Furthermore, the pre-baking conditions are as follows: Baking temperature: 80-100℃, time: 5-15 minutes.
[0059] After vacuum degassing, heating is initiated without removing the vacuum for pre-baking. The pre-baking conditions are: baking temperature 80-100℃ (preferably 90℃ in this embodiment), and holding time 5-15 minutes (preferably 10 minutes in this embodiment). The purpose of pre-baking is to allow some of the solvent in the liquid adhesive to evaporate, causing the resin to undergo initial cross-linking and reach a semi-cured state (B-stage). At this point, the adhesive has completely filled the circuit gaps and is initially shaped, with a certain degree of tackiness on the surface but no longer flowing, preparing for subsequent lamination with the second functional cover film.
[0060] Furthermore, after the liquid adhesive is filled and pressed, the surface flatness reaches ≤10μm / 10mm, and there are no air bubbles or voids.
[0061] After pre-baking, the filling effect can be sampled and tested. Optionally, after vacuum treatment, pre-baking, and subsequent lamination, the liquid adhesive-filled area should meet the following quality requirements: surface flatness ≤10μm / 10mm, and no bubbles or voids observed under a microscope. This flatness requirement ensures tight adhesion between layers during subsequent lamination, without localized stress concentration; the absence of bubbles and voids ensures the uniformity of interlayer bonding and long-term reliability.
[0062] Surface flatness ≤10μm / 10mm and the absence of air bubbles and voids are key indicators for ensuring the reliability of the final product. It is recommended to verify these requirements during the process development stage using microsection analysis and surface profilometry, and adjust printing thickness, vacuum time, or pre-baking parameters as needed to achieve optimal results.
[0063] Furthermore, the liquid adhesive is a liquid acrylic adhesive or epoxy resin adhesive.
[0064] Liquid acrylic adhesives are characterized by good flexibility and strong adhesion to PI films, making them suitable for flexible circuit boards that require bending. Liquid epoxy adhesives, on the other hand, offer higher heat resistance and bonding strength, making them suitable for applications with higher reliability requirements. The appropriate adhesive can be selected based on specific product needs.
[0065] Step S600: Preparation of the second functional coating film: The second functional cover film is prepared in exactly the same way as in step S200, that is, using the same materials, process parameters and steps to form a second functional cover film with the same shielding structure.
[0066] Step S700: Overall pressing: Overall pressing diagram as shown Figure 8As shown, the second functional cover film 20 obtained in step S600 is stacked on the surface of the liquid adhesive layer 700 pre-baked in step S500, ensuring alignment. Then, it is fed into a press for final pressing. The pressing process parameters can be those of existing thick copper circuit FPC pressing parameters, such as: temperature 170℃, pressure 2.0MPa, time 90 minutes for the full-pressure curing stage. During pressing, a PET release film 801 and a silicone rubber replica film 802 are used for buffering and protection to prevent sticking, and pressure is ensured uniformly by pressing with a steel plate 803. After pressing, the second functional cover film 20, the thick copper circuit layer 502, the adhesive layer 600, the liquid adhesive layer 700, and the first functional cover film 10 are integrated to form the final multilayer flexible circuit board structure. A schematic diagram of the final overall structure is shown below. Figure 9 As shown, at this point, the adhesive layer 600 and the liquid adhesive layer 700 are fused together.
[0067] A slice image of the final product of the high-current-carrying, high-shield flexible circuit board for intelligent connected vehicles manufactured according to the method of this embodiment is shown below. Figure 10 and Figure 11 As shown in the figure, the method of this embodiment of the invention achieves the following: Improved shielding layer quality: The silver paste is printed and cured on an independent, flat cover film, resulting in good uniformity and integrity. It is first encapsulated by the cover film and then buffered by the force during the subsequent pressing process, avoiding cracking due to direct pressure.
[0068] Enhanced structural reliability: The "water-based adhesive" effectively fills the gaps and differences between thick copper lines, making the subsequent lamination surface smoother and greatly improving the interlayer bonding force and overall structural strength.
[0069] This improved process, through process reengineering, places the silver paste shielding layer fabrication in a flat initial environment and utilizes water-based adhesive as a gap-filling medium, systematically overcoming the quality and reliability challenges of the shielding layer caused by the unevenness of thick copper lines in traditional processes. Specifically, by pre-fabricating the silver paste shielding layer on a flat cover film, the uneven printing problem caused by the unevenness of thick copper lines in traditional processes is avoided. The silver paste layer is uniform and complete, and is encapsulated and protected by the cover film, providing stress buffering during subsequent pressing and reducing the likelihood of cracking. Simultaneously, liquid adhesive is used to fill the gaps between thick copper lines, allowing the adhesive to fully penetrate deep into the gaps. After curing, there are no voids or air bubbles between the lines, significantly improving surface flatness (up to ≤10μm / 10mm) and achieving an interlayer peel strength ≥0.8N / mm. The resulting flexible circuit board exhibits good shielding performance consistency and high structural reliability, meeting the stringent requirements of intelligent connected vehicles for high current-carrying and highly shielded flexible circuit boards. It is particularly suitable for scenarios such as vehicle power modules and sensor interfaces that require high current transmission and electromagnetic shielding.
[0070] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made under the inventive concept of the present invention using the description and drawings of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A method for manufacturing a high-current-carrying, highly shielded flexible circuit board for intelligent connected vehicles, characterized in that, The method includes the following steps: S100: The first cover film is subjected to plasma activation treatment, wherein the first cover film is an adhesive-free cover film; S200: A silver paste shielding layer is formed on the surface of the first cover film after activation treatment, and the silver paste shielding layer is encapsulated between the first cover film and the second cover film using a second cover film to form a first functional cover film with a shielding structure. S300: Thick copper foil is laminated onto one side of the first functional cover film using an adhesive layer; S400: Performs pattern transfer and etching on the laminated thick copper foil to form a thick copper circuit pattern; S500: Liquid adhesive is printed on the surface where thick copper circuit patterns are formed, so that the liquid adhesive fills the gaps between the thick copper circuits, and pre-baking is performed to make it reach a semi-cured state. S600: Fabricate a second functional cover film with a shielding structure, the structure of the second functional cover film being the same as that of the first functional cover film; S700: The second functional cover film is stacked on the surface of the pre-baked liquid adhesive and pressed together to combine the second functional cover film, the thick copper circuit layer and the first functional cover film into one, forming a flexible circuit board structure.
2. The manufacturing method according to claim 1, characterized in that, The step of fabricating a silver paste shielding layer on the surface of a first cover film after activation treatment, and encapsulating the silver paste shielding layer between the first cover film and the second cover film with a second cover film, includes: The first cover film, after being activated by plasma, is placed on a support plate, and silver paste is printed on the surface of the first cover film to form a shielding layer. The printed silver paste is baked and cured; A second cover film is attached to the surface of the cured silver paste layer. The second cover film is an adhesive cover film, so that the silver paste layer is encapsulated between the first cover film and the second cover film. Remove the support plate to form a first functional cover film with a shielding structure.
3. The manufacturing method according to claim 1, characterized in that, The process parameters for the plasma activation treatment are as follows: Processing power 80-150W, processing time 3-5 minutes, working gas is oxygen, argon or a mixture of oxygen and argon, gas flow rate 50-200sccm, working pressure 50-200mTorr.
4. The manufacturing method according to claim 2, characterized in that, The thickness of the silver paste layer is 8-15 μm. The conditions for baking and curing the printed silver paste are as follows: bake and cure at 120-150℃ for 10-30 minutes.
5. The manufacturing method according to claim 1, characterized in that, The thickness of the printed wet film of the liquid adhesive is 0.5-0.8 times the thickness of the thick copper foil, and its viscosity is 5-15 Pa·s at 25°C.
6. The manufacturing method according to claim 1, characterized in that, The vacuum degree of the vacuum treatment is controlled at ≤-0.08MPa gauge pressure or ≤20Pa absolute pressure, and the pressure holding time is 3-5 minutes.
7. The manufacturing method according to claim 1, characterized in that, The pre-baking conditions are as follows: Baking temperature: 80-100℃, time: 5-15 minutes.
8. The manufacturing method according to claim 1, characterized in that, After plasma activation treatment and before printing silver paste, the surface contact angle of the first cover film drops to below 30°.
9. The manufacturing method according to claim 1, characterized in that, After the liquid adhesive is filled and pressed, the surface flatness reaches ≤10μm / 10mm, and there are no air bubbles or voids.
10. The manufacturing method according to claim 1, characterized in that, The liquid adhesive is a liquid acrylic adhesive or epoxy resin adhesive.